PENGARUH PROGRAM MATA NAJWA MELALUI MEDIA SOSIAL TERHADAP SIKAP POLITIK REMAJA DI DESA SEPANJANG KECAMTAN GLENMORE KABUPATEN BANYUWANGI - tulloh, ferdian rohmad; suyono (Universitas Muhammadiyah Jember, 2024)
Abstract This study aims to evaluate the influence of the Mata Najwa program through social media on the political attitudes of adolescents in Sepanjang Village, Glenmore District, Banyuwangi Regency. The rapid development of information anditechnology, especially through social media, has opened up space for political participation for teenagers. This quantitative research aim to examine the nfluence of the Mata Najwa program on social media on adolescents' political attitudes, based on the Uses and Effect Theory. The results of a study in Sepanjang Village, Banyuwangi, show that the